Semiotic Analysis of Symbols in Andrea Hirata's Laskar Pelangi - Kurniati, Nia; Lestari, Lilia Putri; Sakna, Sabilinnisa' (EDUTECH, 2025)
This study explores the semiotic elements in the novel Laskar Pelangi by Andrea Hirata, focusing on the symbolic representations and their deeper meanings. Employing a qualitative descriptive approach, the data consists of textual evidence from the novel, with a particular focus on recurring symbols and their narrative significance. Roland Barthes' semiotic theory serves as the analytical framework, dissecting symbols into their denotative (literal) and connotative (implied) meanings. Data collection involved close reading of the text, identifying symbolic elements, and categorizing them based on their thematic relevance, such as education, hope, and social inequality. The analysis was supported by secondary sources, including journal articles and literary reviews, to ensure a comprehensive interpretation of the semiotic structures within the text. The findings reveal how the symbols contribute to the overarching themes, providing a deeper understanding of the novel's portrayal of societal issues. This study highlights the significance of semiotics in understanding literary works and the power of symbols in conveying complex social messages.